Pengaruh Citra Merek Melalui Sikap Konsumen Terhadap Niat Beli Ulang Pada Produk Busana Muslim Zoya di Surabaya - Nurul Ain; Ririn Tri Ratnasari (Universitas Airlangga, 2015)
This study aims to determine the effect of brand image to re-purchase intention through attitude of consumers to the brand in the Zoya’s Muslim fashion products in Surabaya.This sudy collects primary data from the questionere with 30 sample. The sample is the consumer of Zoya’s products in Surabaya. This study utilizes Consumer characteristics who have ever made a purchase Zoya’s products in Surabaya within the past year. The sampling technique is accidental and purposive sampling.This study utilizes quantitative approach path analysis technique (path analysis).Endogenous variables is re-purchase intention, whereas exogenous variables is brand image and intervening endogenous variable is the attitude of consumers to the brand image. The results indicates that the brand image has a positive and significant impact to the consumer attitudes on Zoyas’s Muslim fashion brand. Other results shows that a significant influence on consumer attitudes and re-purchase intention . Then, the brand image is also has positive and significant impact on re-purchase intention on the Zoya’s Muslim fashion in Surabaya. Based on these findings, Zoya Surabaya branch should maintain and enhance the brand image of Zoya and positive attitudes of consumers towards the Muslim fashion Zoya so as to improve on the consumer's purchase intention on products Moslem Zoya. For the further research, it will be better by adding a moderator variables such as the level of religious knowledge that will get an idea whether the moderator variables will weaken or increase the influence of consumer attitudes to re-purchase intention of consumers on Zoyas’s Muslimfashion brand.